How to Become a Microcelebrity? Verbal and Non-Verbal Means Used by Streamers of Videogames in Creating Their Image - Janion, Agnieszka (Verbum, 2025)
The article, that aligns with pragmatic and multimodal studies, presents the results of observations regarding measures used by French streamers of videogames in order to be appreciated by the spectators. It seems that the construction of the image (ethos) is an essential element of videogame streamers’ speaking. Indeed, the streamers want to impress their public and even be recognized as microcelebrities, basing not only on their gaming skills. As streaming represents a type of verbal interaction, this image (ethos) depends also on building and maintaining the relationship between the streamer and his public during the show. Having analysed eight streamings, we have noticed some verbal measures (e.g.: language register, sociolect, form of address) and no verbal measures (e.g.: gestures) that contribute to form the images of: host, friend or expert.